Clinical features and predictors of non-cardiac death in patients hospitalised for acute myocardial infarction: Insights from the Tokyo CCU network multicentre registry. (1st May 2023) - Wakabayashi, Kohei; Higuchi, Satoshi; Miyachi, Hideki; Minatsuki, Shun; Ito, Ryosuke; Kondo, Seita; Miyauchi, Katsumi; Yamasaki, Masao; Tanaka, Hiroyuki; Yamashita, Jun; Kishi, Mikio; Abe, Kaito; et al.
Abstract: Background: Patients with acute myocardial infarction (AMI) commonly have multiple comorbidities, and some die in hospitals due to causes other than cardiac complications. However, limited information is available on noncardiac death in patients hospitalised for AMI. Therefore, the present study was performed to determine the incidence, annual trend, clinical characteristics, and predictors of in-hospital non-cardiac death in patients with AMI using the Tokyo Cardiovascular Care Unit (CCU) network registry. Methods: The registry included 38, 589 consecutive patients with AMI who were admitted to the CCU between 2010 and 2019. The primary endpoint was in-hospital noncardiac death. Further, predictors of cardiac and non-cardiac death were identified. Results: The incidence of all-cause in-hospital mortality was 7.0% ( n  = 2700), and the proportion of mortality was 15.6% ( n  = 420) and 84.4% ( n  = 2280) for noncardiac and cardiac causes, respectively. The proportion of noncardiac deaths did not change annually over the last decade ( p  = 0.66). After adjusting for all variables, age, Killip classification grade, peak creatine kinase, hemoglobin, serum creatinine, and C-reactive protein were common predictors of cardiac and non-cardiac deaths. Indicators of malnutrition, such as lower body mass index (kg/m 2 ) [odds 0.94, 95%CI (0.90–0.97), p  < 0.001] and serum low-density lipoprotein cholesterol level (per 10 mg/dl) [odds 0.92, 95%CI (0.89–0.96), p < 0.001] were the specific predictors for non-cardiac deaths. Conclusions: The incidence of in-hospital noncardiac death was significant in patients with AMI, accounting for 15.6% of all in-hospital mortalities. Thus, prevention and management of non-cardiac complications are vital to improve acute-phase outcomes, especially those with predictors of non-cardiac death. Graphical abstract: Clinical Features and Predictors of Non-cardiac Death in Patients Hospitalised for Acute Myocardial Infarction. AMI acute myocardial infarction; CCU Cardiovascular Care Unit; BMI body mass index; LDL-C low-density lipoprotein cholesterol; CRP C-reactive protein; CK creatine kinase; CPA cardiopulmonary arrest; WBC white blood cell; LMCA left main coronary artery; BNP B-type natriuretic peptide. Unlabelled Image Highlights: This study demonstrates the clinical importance of noncardiac death in AMI. No previous study has focused on noncardiac death in patients hospitalised for AMI. Incidence of non-cardiac death was high and has not changed over the last decade. The management of non-cardiac complications with a comprehensive approach is vital. Malnutrition may be a key factor for additional care in patients with AMI.